1992
DOI: 10.2337/diab.41.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of GLUT4 in Skeletal Muscle From Insulin-Resistant Patients With Obesity, IGT, GDM, and NIDDM

Abstract: In obesity, impaired glucose tolerance (IGT), non-insulin-dependent diabetes mellitus (NIDDM), and gestational diabetes mellitus (GDM), defects in glucose transport system activity, contribute to insulin resistance in target tissues. In adipocytes from obese and NIDDM patients, we found that pretranslational suppression of the insulin-responsive GLUT4 glucose transporter isoform is a major cause of cellular insulin resistance; however, whether this process is operative in skeletal muscle is not clear. To addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(53 citation statements)
references
References 40 publications
3
47
2
1
Order By: Relevance
“…It contrasts the normal values reported in other insulin resistant states such as obesity and type 2 diabetes [33,34]. The decrease was not caused by an overall reduction in mRNA levels since the patients had normal levels of b-actin.…”
Section: Discussioncontrasting
confidence: 70%
“…It contrasts the normal values reported in other insulin resistant states such as obesity and type 2 diabetes [33,34]. The decrease was not caused by an overall reduction in mRNA levels since the patients had normal levels of b-actin.…”
Section: Discussioncontrasting
confidence: 70%
“…Tissues obtained under these conditions have yielded high quality RNA for measurement of gene expression in previous studies [8][9][10].…”
Section: Muscle Biopsiesmentioning
confidence: 99%
“…Percutaneous needles biopsies of the vastus lateralis were performed as previously described [7,8]. In each subject, one biopsy was performed under basal conditions after an overnight fast prior to the clamp study, and a second was performed in the contralateral leg after 3 h of steady-state hyperinsulinemia.…”
Section: Muscle Biopsiesmentioning
confidence: 99%
“…In addition, decreases in GLUT4 in adipose tissues but not in skeletal muscles have been reported in NIDDM and obese patients (Garvey et al, 1991(Garvey et al, , 1992. Recently, Miura et al revealed that the high-fat diet responsive cis-element (HFRE) located in GLUT4 gene is responsible for the adipocyte-specific down regulation of GLUT4 by high-fat diet.…”
Section: Discussionmentioning
confidence: 94%